ACADEMIC CHEATING BEHAVIOR REVIEWED FROM NEUTRALIZATION OF CHEATING BEHAVIOR AND GENDER OF THE ACCOUNTING STUDENTS AT UNIVERSITIES IN BATAM - Mia Yasmin Belinda; Hajan Hidayat (Pusat P2M Politeknik Negeri Batam, 2018)
This study aimed to determine the neutralization relationship with the academic cheating behavior and differences in students perceptions of male and female on neutralization who is do cheating behaviors in academic studies. The sampling method used purposive sampling techniques. The subjects were as 378 who is take the accounting courses with accredited B (Good) in several universities in Batam. The questionnaires were distributed to each universities about 125 questionnaires. Hypothesis testing used a Pearson product moment correlation analysis and t-test Independent test. The results of this study found that, there is a strong positive correlation between neutralization with the academic cheating behavior with a correlation coefficient r = 0,829 with probability p = 0.000 (P <0.05). The results of the study for the t-test Independent test showed that there are differences in perception between male students and female with an average of male students is higher by 63.79% and the female with a percentage of 35.03%. Moreover, the conclusion for further study, it can carry out educational purpose suppress the neutralization process, ethics education should consider the perspective of male and female, and study the factors affecting the dynamics of neutralization and neutralization of both male and female.